2015
DOI: 10.4238/2015.february.6.17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of concentrations of botulinum toxin A for the treatment of hemifacial spasm: a randomized double-blind crossover trial

Abstract: ABSTRACT. The aim of our study was to evaluate the efficacy and safety of two concentrations of botulinum toxin A (BTX-A) for the treatment of hemifacial spasm. We randomly divided 20 patients with hemifacial spasm into high-and low-concentration groups; they were administered 50 and 25 U/mL BTX-A injection, respectively. Further, we compared the curative effects and the occurrence of adverse reactions in the two groups. Our results showed that both the concentrations of BTX-A were effective and no significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Injecting BoNT/A in a lower concentration and in a larger volume has been shown to enlarge the area of effect compared to injections of higher concentration and smaller volume [ 92 96 ]. In addition, lower concentration has been associated with stronger clinical effect [ 94 ], but no difference in clinical efficacy between low and high concentrations has also been reported [ 93 , 97 ]. Higher concentration has been associated with effect of longer duration but also with more adverse events [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Injecting BoNT/A in a lower concentration and in a larger volume has been shown to enlarge the area of effect compared to injections of higher concentration and smaller volume [ 92 96 ]. In addition, lower concentration has been associated with stronger clinical effect [ 94 ], but no difference in clinical efficacy between low and high concentrations has also been reported [ 93 , 97 ]. Higher concentration has been associated with effect of longer duration but also with more adverse events [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lower concentration has been associated with stronger clinical effect [ 94 ], but no difference in clinical efficacy between low and high concentrations has also been reported [ 93 , 97 ]. Higher concentration has been associated with effect of longer duration but also with more adverse events [ 97 ]. We reconstituted the toxin to a concentration of 100IU/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 shows two randomised controlled trials and two interventional studies on LAN for hemifacial spasm, one randomised controlled trial [ 10 ] and one interventional study [ 12 ] by comparing LAN and ONA, and no difference in efficacy and safety was found when converted on a LAN and ONA dose conversion ratio of 1:1. One randomised controlled trial [ 20 ] showed additional posterior auricular muscle injections can reduce acoustic symptoms, and one interventional study [ 21 ] showed that the LAN dose of 50 MU/mL produces longer therapeutic effects and more adverse effects than that of 25 MU/mL whereas the peak efficacies at these two doses are identical.…”
Section: Resultsmentioning
confidence: 99%
“…The mean duration of the effect was around 12 weeks. There were three RCT studies, of which two were conducted to investigate the efficacy and safety of BoNT in HFS [36,37]. The third study compared pretarsal versus preseptal injections of the orbicularis oculi in 31 patients with HFS reporting that the pretarsal portion of the orbicularis oculi was associated with a significantly high response rate in terms of latency to response, duration of improvement, Jankovic Rating Scale (JRS), self-response scale, and patient satisfaction scale than the preseptal injections [38].…”
Section: Reported Trials-evidence-based Medicinementioning
confidence: 99%